High gravity ethanol fermentation from cassava chips - Suttikul, Suthkamol; Panthong, Jutamas; Panphan, Vishnu; Kanhanont, Thapparait (Asia-Pacific Journal of Science and Technology, 2020)
Very high gravity (VHG) ethanol fermentation has been developed to enhance productivity through higher ethanol concentration. The advantages of this technology offer great savings in process water and energy requirements through fermentation of higher concentrations of substrate, therefore, increased final ethanol concentration in the medium. The technology also allows increased fermentation capacity, without major alterations to existing facilities, by efficient utilization of fermenter space. In addition, ethanol production at high temperature has several advantages, such as reduced cooling costs and reduced risk of contaminations. Simultaneous saccharification and fermentation (SSF) of cassava chips under high gravity ethanol fermentation was studied. Cassava chips were ground into small granules and dissolved in water to reach 30% (w/w) of dry solid. Mash viscosity was reduced by the pretreatment with viscosity reduction enzyme. Starch in the pretreated mash was liquefied to maltodextrins by the action of thermo-stable - amylase (0.1%, w/w) at 85oC for 90 min. SSF of liquefied mash was performed at 35oC with the simultaneous addition of glucoamylase, thermotorelant yeast and 0.5 g/L of urea as a nitrogen source for the yeast. The optimal glucoamylase loading was 0.6% (w/w). Under these conditions, the SSF process finished after 60 h. The ethanol content achieved 117.17±1.44 g/L or 14.85% (v/v) corresponding to 85.56% of the theoretical ethanol yield.